Perbandingan Efektivitas Penggunaan Tepung Tapioka Dan Tepung Sagu Sebagai Bahan Perekat Briket Batok Kelapa - Herwin A. Hi. Adam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Coconut shell charcoal briquettes have several advantages compared to other conventional solid fuels, including being able to produce high heat, no smoke, longer burning time/flame, has the potential to be a substitute for coal, and is more environmentally friendly. The aim of the research is to determine the comparison of adhesives in terms of triggering time, burning time and physical quality of the briquettes. The type of research used is an experimental method using a Non-Probability Sampling design with the Qouta Sample method. The results of testing the triggering time of briquettes with tapioca flour adhesive with a faster triggering time for 15 minutes 22 seconds while sago flour is 15 minutes 45 seconds. From the results of observations of the long burning test for briquettes with tapioca flour adhesive which is of better quality with a long burning time of 3 hours 50 minutes while for sago flour it is 3 hours 10 minutes. And from the results of the physical quality test of briquettes with Tapioca flour adhesive and sago flour adhesive both had the same results. The results of the test concluded that charcoal briquettes with tapioca flour adhesive were of higher quality in terms of triggering time, burning time and physical quality. Suggestions for the public are to use tapioca flour as an adhesive for coconut shell charcoal briquettes because it produces heat that lasts a long time without smoking and ignites quickly.